Decolonial interventions in the postwar politics of Japanese education: Reassessing the place of Shinto in Japanese language and moral education curriculum - Takayama, Keita (Revista Española de Educación Comparada, 2023)
Much of postwar politics in Japanese education has revolved around the tensions between conservative’s retrogressive desire for the imperial past on the one hand and the liberal-left’s progressive agenda on the other. The former demands a return to the teaching of traditional (Confucius) family values, patriotism and Shinto-inspired reverence (awe) towards the universe, while the latter demands teaching for rational, critical minds deemed essential for democratic citizenship. This binary structure of political contestation is increasingly problematized by the emerging political sensibilities around the ecological crisis and eco-feminist critique of human exceptionalism, hype-separation between human and nature and ontological individualism. The chapter demonstrates how the new ecological and decolonial literature demands a fundamental rethinking of the postwar politics of Japanese education, in particular, in relation to the place of Shinto—the Japanese indigenous belief system—in school curriculum. It exposes the limitations of the postwar liberal-left discourse which has reduced Shinto to nothing but the conservatives’ retrogressive desire to ‘return.’ The chapter concludes, drawing on Chen’s (2010) notion of de-cold-war politics, that the Cold War framing of education policy debate must be overcome to unleash the decolonial and ecological potentials of Japanese education towards addressing the pressing sustainable challenges today.